E- SERVICE QUALITY IZIN PRAKTIK DOKTER (UMUM, SPESIALIS DAN GIGI) PADA APLIKASI E-PINTER DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN BENGKALIS - Yunita Kitrin; Eko Handrian (YUDABBIRU JURNAL ADMINISTRASI NEGARA, 2022)
This study discusses the electronic service quality (e-service quality) of doctor's practice licenses (general, specialist and dental) in the e-smart application at the investment office and one-stop integrated service in Bengkalis Regency. This study aims to determine the quality of online services (e-service quality) provided by the investment department and one-stop integrated services that have met the expectations of the community in simplifying and shortening service time. This type of research uses descriptive quantitative methods where primary data is obtained through observation and questionnaires, and secondary data is obtained through interviews with respondents. In this study, the author uses the theory of e-service quality proposed by Parasuraman, et.al which contains 4 dimensions that make up a quality e-service, namely efficiency, fulfillment, system availability, and privacy. The results showed that the e-service quality of doctor's practice licenses (general, specialist and dental) in the e-smart application at the investment office and one-stop integrated service in Bengkalis Regency had a fairly good service quality, because in providing online services there were still found permit applicants who do not understand the procedures for using applications in online licensing arrangements, there are still services that are not in accordance with service standards and standard operating procedures, some obstacles such as network disturbances that hinder business actors from taking care of licensing in the application. So looking at these conditions, it is hoped that the service should further improve the quality of services such as providing guidebooks on the procedures for using the e-smart system, for responsiveness the agency should provide media that is often used by the community such as whatsapp and for network stability the service should improve performance a server that is added with a load balance so that the network is connected stably.